Effects of Artemisia annua supplementation on the performance and gut health of laying hens challenged with mixed Eimeria species - Sharma, Milan Kumar; Liu, Guanchen; Choppa, Venkata Sesha Reddy; Rafieian-Naeini, Hamid Reza; Mahdavi, Fatemeh Sadat; Marshall, Brett; Gogal, Robert M.; Kim, Woo Kyun (Frontiers in Physiology, 2024)
Background: Coccidiosis outbreaks in susceptible laying hens can significantly drop egg production and cause a substantial economic loss to the egg industry. Therefore, effective strategies to control coccidiosis are needed, and Artemisia annua (AA) might have the potential to be a phytogenic feed additive, an alternative to anticoccidial agents. This study aimed to investigate the effect of dietary supplementation of powdered AA on the performance and gut health of laying hens infected with coccidiosis by Eimeria spp. Methods: A total of 225 Hy-Line W-36 laying hens at 23 weeks of age were allocated into five treatment groups: (i) control (NC), (ii) pair-fed control (PF), (iii) challenged control (CC), (iv) CC with dietary inclusion of 0.5% AA (0.5AA) and (v) CC with dietary inclusion of 1% AA (1AA). The hens grouped in CC, 0.5AA, and 1AA were orally inoculated with sporulated oocysts of E. maxima (12,500), E. tenella (12,500), and E. acervulina (62,500) at week 25. The PF hens received the same amount of feed consumed by CC from 0-14 days post-inoculation (dpi). The performance of the laying hens was measured weekly, and gut permeability, lesion score, intestinal morphometry, and immunity were evaluated. Results: At 6 and 14 DPI, laying hens challenged with Eimeria spp. had a lower BW than PF and NC (P<0.0001). Supplementation of 1% AA improved the HDEP by 8.1% compared to CC; however, it is still 15.4% lower than PF (P<0.0001). The inclusion of 1% AA did not have any beneficial effect on FI; however, FCR was improved by 0.61 (2.46) than that of CC (3.07; P<0.0001). The inclusion of 1% AA reduced the severity of the intestinal lesions and increased the recovery of intestinal villi (P<0.05). Additionally, gut permeability was significantly different between challenged and non-challenged hens; however, among the challenged hens, the inclusion of AA reduced the gut permeability by 29% compared to CC (P<0.0001). Furthermore, the inclusion of 0.5% AA reduced the inflammatory responses in infected hens. Conclusion: Dietary inclusion of AA partially restored the laying hens' performance and gut health and modulated the inflammatory immune response of laying hens following Eimeria infection.